Medical and obstetric factors associated with preterm deliveries among women of childbearing age at Pumwani maternity hospital, Nairobi County, Kenya - Mwangi, Daniel K.; Waithaka, Stanley K.; Odongo, Alfred O. (International Journal Of Community Medicine And Public Health, 2021)
Background: The rate of pre-term birth (PTB) in Kenya stands at 12.3%. Preterm deliveries are associated with high neonatal mortality and have a huge financial burden on the parents and the government. Prematurity is also associated with chronic diseases like diabetes and hypertension in adult life. The study objective was to determine the medical1and obstetric factors1associated1with preterm deliveries among women of childbearing age (15-49 years) at Pumwani maternity hospital (PMH). Methods: A hospital-based cross-sectional study was conducted among 191 mothers of reproductive age (15-49 years) who delivered at PMH during the study period. Data was collected using a questionnaire and a data abstraction tool. Descriptive statistics were used to summarize categorical variables. Chi-square was used to test for the strengths of associations. Prevalence adjusted odds ratios (PAOR) were used to estimate the strengths of associations. Results: The study found that the association between past pregnancy (p=1.0), history of surgery (p=1.0), medication (p=1.0), urinary tract infection (p=0.453), miscarriage (p=1.0) and chronic disease (p=0.395) and preterm delivery among women of child bearing age (15-49 years) at PMH was not statistically significant. The association between premature delivery (p=0.021), parity (p=0.000), premature rapture of membranes (PROM) (p=0.000), antepartum hemorrhage (APH) (p=0.045), cervical incompetence (p=0.001), pre-eclampsia toxemia (PET) (p=0.000), and placenta abruption complications (p=0.009) and preterm delivery was statistically significant. Conclusions: The association between premature delivery, parity, PROM, APH, cervical incompetence, PET and placenta abruption complications and preterm delivery was statistically significant.